Tools for prioritizing Ecosystem Services provided by fragments forest in the context of cities - da Silva, Alessandra Leite [UNESP]; Ribeiro, Admilson Írio [UNESP]; Longo, Regina Márcia (FapUNIFESP (SciELO), 2021)
Forest remnants are essential in the provision of ecosystem services in cities. However, adequate ecological parameters are still needed to assess them. Because of this, the present work proposes a methodology for assessing the potential of providing ecosystem services by forest remnants in urban watershed based on the application and interpretation of landscape spatial metrics used in Landscape Ecology studies. For that, the environmental indicators (area, central area, circularity index, distance from the nearest neighbor, water springs, land use, and occupation in the surroundings) were evaluated in GIS software and to them, the Hierarchical Process Analysis Method (AHP) was applied to identify the importance of each parameter in the provision of ecosystem services and the priority in each remainder. The study was carried out in a watershed in Campinas/ SP, in which it was found that forest remnants develop, primarily, ecosystem support or habitat services, regulation services, and cultural services.
Herramientas para priorizar los Servicios Ecosistémicos prestados por fragmentos forestales en el contexto de las ciudad0es
Ferramentas para priorização dos serviços ecossistêmicos prestados por fragmentos florestais no contexto das cidad0es
Keywords: análise espacial; Análise Hierárquica de Processos; análisis espacial; Análisis Jerárquico de Procesos; ecosystem services; Hierarchical Analysis of Processes; Remanentes forestales urbanos; Remanescentes florestais urbanos; servicios ecosistémicos; serviços ecossistêmicos; spatial analysis; Urban forest remnants